Effects of High-Intensity Interval vs. Moderate-Intensity Continuous Training on Cardiac Rehabilitation in Patients With Cardiovascular Disease: A Systematic Review and Meta-Analysis - Yue, Tian; Wang, Yan; Liu, Hui; Kong, Zhaowei; Qi, Fengxue (Frontiers in Cardiovascular Medicine, 2022)
Background Studies have shown that high-intensity interval training (HIIT) is superior to moderate-intensity continuous training (MICT) for increasing peak oxygen uptake (VO2peak) and reducing cardiovascular disease (CVD) and mortality. To our knowledge, previously published systematic reviews have neither compared different HIIT models with MICT nor investigated intervention frequencies of HIIT vs. MICT for purposes of improving cardiorespiratory fitness in patients with CVD. Objective The purpose of this meta-analysis was to compare the effects of different training models, intervention frequencies and weeks of HIIT vs. MICT on changes in cardiorespiratory fitness during cardiac rehabilitation (CR). Methods A systematic search was carried out for research articles on randomized controlled trials (RCTs) indexed in the PubMed, Cochrane Library, Web of Science, Embase and Scopus databases for the period up to December 2021. We searched for RCTs that compared the effect of HIIT vs. MICT on cardiorespiratory fitness in patients with CVD. Results Twenty-two studies with 949 participants (HIIT: 476, MICT: 473) met the inclusion criteria. Sensitivity analysis revealed that HIIT increased VO2peak more than MICT (MD = 1.35). In the training models and durations, there was a greater increase in VO2peak with medium-interval HIIT (MD = 4.02) and more than 12 weeks duration (MD = 2.35) than with MICT. There were significant improvements in VO2peak with a HIIT frequency of 3 times/week (MD = 1.28). Overall, one minor cardiovascular and four non-cardiovascular adverse events were reported in the HIIT group, while six non-cardiovascular adverse events were reported in the MICT group. Conclusion HIIT is safe and appears to be more effective than MICT for improving cardiorespiratory fitness in patients with CVD. Medium-interval HIIT 3 times/week for more than 12 weeks resulted in the largest improvement in cardiorespiratory fitness during CR. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021245810, identifier: CRD42021245810.